The Effectiveness Of Nanoscience Activities In Improving Secondary School Students’ Attitude, Relevance, And Understanding Of Chemistry Concepts - Chua , Kah Heng (2018)
Laboratory activities is seen as an essential part of teaching and learning of chemistry. In chemistry lessons, teacher is trying to extend students’ knowledge and develop their understanding of the ideas, theories and models that chemists have found useful in explaining and predicting its behaviour. At the same time foster a positive attitude towards chemistry lessons and increase the relevance of chemistry education among students.